An examination of the implementation of the World Health Organisation's anti-tuberculosis treatment, the Directly Observed Treatment Short Course (DOTS), in poor South African communities - Jacobs, Nasolo Monifa (Social Anthropology, 2023)
This dissertation examines the implementation of the anti-tuberculosis treatment, the Directly Observed Treatment Short Course, of the World Health Organisation (WHO) in poor South African communities. Research for this dissertation was carried out over a two-year period in one poor community, a tuberculosis (TB) quarantine hospital and several primary care clinics. This dissertation argues that the DOTS programme is culturally inappropriate and consequently unsuccessful in meeting the WHO's TB treatment targets. It will show that the design of the DOTS programme assumes access to basic resources such as food and shelter and focuses its attE11tion on ensuring regular access to anti-TB medication. However, TB patients in many poor South African communities do not have access to basic resources and thus experience the DOTS programme and the treatment protocol as a burden. Although TB patients face these challenges to meeting their treatment goals, many of them view the DOTS programme in their communities as a source of resources from which they can access jobs, food, money and general social services. The thesis will demonstrate that there is a wide gap between what the DOTS programme offers and what the TB patients and community members expect. It will also show that this gap limits the ability of TB patients to adhere to the treatment and thus renders the DOTS programme culturally inappropriate and unsuccessful in these South African communities.